Knowledge and Perception of COVID-19 Pandemic during the First Wave: a Cross-Sectional Study among Nepalese Healthcare Workers (Tribhuvan University Journal of Microbiology, 2021)
Objectives: This study aimed to assess knowledge and perception of COVID 19 among frontline health care workers in Nepal.Methods: A web-based cross-sectional study was conducted among frontline healthcare workers involved in managing and treating COVID-19 in Nepal by adapting the questionnaire from the World Health Organization. Data were analyzed using the Statistical Package for Social Science version 26.0. A chi-square test was used to investigate the association level among variables at 95% level of significance.Results: A total of 285 health professionals participated in this study, among them male (50.5%), and female (49.5%). The mean (± SD) age of participants was 27.21 ± 5.42 years old. Most of the participants got information on COVID-19 from social media (50.5%) and online news/newspapers (40.3%). On the other hand, a significant proportion of Health care workers (HCWs) had poor knowledge about its transmission (n=170, 59.6%) and an incubation period (n=129, 45.3%).Conclusion: There was a significant gap in knowledge and perception, particularly about the transmission and incubation period. A concerned national initiative to respond the pandemic could help better compliance with behavioral guidelines to respond to this public health emergency.